Transcatheter Embolization of the Inferior Epigastric Artery: Technique and Clinical Outcomes. (April 2021) - Diamantopoulos, Athanasios; Mulholland, Douglas; Katsanos, Konstantinos; Ahmed, Irfan; McGrath, Andrew; Karunanithy, Narayan; Sabharwal, Tarun
Purpose: Symptomatic rectus muscle sheath hematoma may be the result of bleeding originating from the inferior epigastric artery. We report the technique and the results from a series of consecutive patients treated by transcatheter embolization, evaluating both ipsilateral and contralateral retrograde approaches. Methods: This was a retrospective study including patients with verified rectus muscle sheath hematoma as a result of active extravasation from the inferior epigastric artery referred for transcatheter embolization. Technical success, clinical success and major complications were calculated. In addition, minor complications, blood transfusions required after a technically successful embolization, length of stay, peri-procedural and 30-day mortality and overall survival at 6 months were obtained. All statistical analysis was performed using SPSS. Results: Twenty-one patients (mean age = 59.67 ± 19.51 years old) were included. The cause of the bleeding in the vast majority was iatrogenic trauma (n = 12/21, 57.14%). Both contralateral (n = 12/21, 57.14%%) and ipsilateral (n = 9/21, 42.86%) retrograde approaches were used. Embolic materials included micro-coils (n = 13/20, 65%), microspheres (PVA) (n = 1/20, 5%), a combination of PVA and micro-coils (n = 5/20, 25%) and gel-foam (n = 1/20, 5%). Overall technical success was 95.2% (n = 20/21) while clinical success was achieved in all but one of the technically successful cases 95% (n = 19/20). One patient died peri-procedurally due to profound hemodynamic shock. There were no other major complications. Additional transfusion was necessary in 7 patients (n = 7/21, 33.33%). There was a significant increase in the hemoglobin levels after the embolization (7.03 ± 1.78 g/dL pre-procedure Vs 10.91 ± 1.7 g/dL post-procedure, p = 0.048). The median hospital stay was 8 days. The peri-procedure and 30-day mortality was 4.8% (n = 1/21) and 28.6% (n = 6/21) respectively. The 6-month survival was 61.9% (13/21). Conclusion: Percutaneous embolization of the inferior epigastric artery is a minimally invasive method with satisfactory results. Both ipsilateral and contralateral retrograde approaches are feasible.